2014
DOI: 10.1186/1471-2466-14-115
|View full text |Cite
|
Sign up to set email alerts
|

Short-term glutamine supplementation decreases lung inflammation and the receptor for advanced glycation end-products expression in direct acute lung injury in mice

Abstract: BackgroundGlutamine (GLN) has been reported to improve clinical and experimental sepsis outcomes. However, the mechanisms underlying the actions of GLN remain unclear, and may depend upon the route of GLN administration and the model of acute lung injury (ALI) used. The aim of this study was to investigate whether short-term GLN supplementation had an ameliorative effect on the inflammation induced by direct acid and lipopolysaccharide (LPS) challenge in mice.MethodsFemale BALB/c mice were divided into two gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Two and 18 h after induction of lung injury, glutamine prevented morphological changes in the lung parenchyma and neutrophil infiltration in the alveolar space, enhanced reduced glutathione (GSH) synthesis, attenuated interleukin (IL)-8 release in lung tissue, and prevented higher CD11b expression in blood neutrophils [ 53 ]. Another study performed in mice fed a glutamine-supplemented diet (0.8 g/kg body weight from feed conversion) 10 days before intratracheal administration of hydrochloric acid plus E. coli LPS-induced ARDS showed that glutamine pretreatment reduced levels of the receptor for advanced glycation end-products (RAGE) and interleukin (IL)-1β in bronchoalveolar lavage fluid (BALF), with corresponding decreases in mRNA expression [ 54 ]. In a two-hit model of hydrochloric acid aspiration plus injurious mechanical ventilation, intravenous glutamine, administered 30 min before the randomization for recruitment maneuver and soon after inducing acid aspiration, improved lung morphofunction as well as neutrophil recruitment and cytokine production in lung tissue [ 55 ].…”
Section: Glutamine Therapy In Respiratory Diseasesmentioning
confidence: 99%
“…Two and 18 h after induction of lung injury, glutamine prevented morphological changes in the lung parenchyma and neutrophil infiltration in the alveolar space, enhanced reduced glutathione (GSH) synthesis, attenuated interleukin (IL)-8 release in lung tissue, and prevented higher CD11b expression in blood neutrophils [ 53 ]. Another study performed in mice fed a glutamine-supplemented diet (0.8 g/kg body weight from feed conversion) 10 days before intratracheal administration of hydrochloric acid plus E. coli LPS-induced ARDS showed that glutamine pretreatment reduced levels of the receptor for advanced glycation end-products (RAGE) and interleukin (IL)-1β in bronchoalveolar lavage fluid (BALF), with corresponding decreases in mRNA expression [ 54 ]. In a two-hit model of hydrochloric acid aspiration plus injurious mechanical ventilation, intravenous glutamine, administered 30 min before the randomization for recruitment maneuver and soon after inducing acid aspiration, improved lung morphofunction as well as neutrophil recruitment and cytokine production in lung tissue [ 55 ].…”
Section: Glutamine Therapy In Respiratory Diseasesmentioning
confidence: 99%
“…Here, we tested the hypothesis that 4% glutamine supplementation in mice with SSADHD would be therapeutically beneficial via restoration of brain neurotransmitter homeostasis. 4% glutamine supplementation has been shown to promote rescuing effects in several mouse models . Since low glutamine levels were reported as early as post‐natal day of life (P) 3, we postulated that glutamine deficiency occurred already during fetal life and chose to begin supplementation during the prenatal period via maternal supplementation, with continuation throughout weaning and until P30.…”
Section: Introductionmentioning
confidence: 99%
“…4% glutamine supplementation has been shown to promote rescuing effects in several mouse models. [6][7][8] Since low glutamine levels were reported as early as post-natal day of life (P) 3, 2 we postulated that glutamine deficiency occurred already during fetal life and chose to begin supplementation during the prenatal period via maternal supplementation, with continuation throughout weaning and until P30. Prenatal supplementation of nutrients and other amino acids has proven to be effective in other animal studies in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of acute lung injury, a few studies have shown a beneficial effect of Gln supplementation 26,27 , while others have deemed Gln inhibition to be important for preventing progression following injury 28 . In the case of TB, Mtb infection has been shown to induce glutamine metabolism transcripts 29,30 .…”
Section: Discussionmentioning
confidence: 99%